2010
DOI: 10.1007/s12032-010-9544-x
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent administration of liposomal doxorubicin improves the survival of patients with invasive bladder cancer undergoing hypofractionated accelerated radiotherapy (HypoARC)

Abstract: Cisplatin-based radio-chemotherapy is an effective alternative to cystectomy. The position of cisplatin has been challenged by novel drugs, while altered radiotherapy fractionation is also tested against conventional radiotherapy (RT). This study focuses on liposomal doxorubicin (LDox) in combination with an aggressive radiotherapy scheme (HypoARC). Eighty-two bladder cancer patients were treated with hypofractionated/accelerated RT (14×2.7 Gy to the pelvis and 15×3.4 Gy to the bladder, within 19 days), suppor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Drug delivery systems have not extensively been studied in the treatment of bladder cancer. Panteliadou et al reported a significant overall survival benefit in MIBC patients when Doxil was added to an aggressive radiotherapy scheme, with two-year overall survival rates of 58.7% vs. 86.5%, p ¼ .04, respectively [52]. However, whether Doxil or other liposomal formulations are superior to systemic free chemotherapy in the treatment of MIBC patients is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Drug delivery systems have not extensively been studied in the treatment of bladder cancer. Panteliadou et al reported a significant overall survival benefit in MIBC patients when Doxil was added to an aggressive radiotherapy scheme, with two-year overall survival rates of 58.7% vs. 86.5%, p ¼ .04, respectively [52]. However, whether Doxil or other liposomal formulations are superior to systemic free chemotherapy in the treatment of MIBC patients is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Further trials studying radiation therapy with various radiosensitizing agents have been performed since. These studies have investigated single-agents (cisplatin [22] , gemcitabine [23] , vinblastine [24] , amifostine [25] , liposomal doxorubicin [26] ) and combinations (cisplatin-paclitaxel [27] , cisplatin-5FU [28] , carbogen-nicotinamide [29] ).…”
Section: Localized Muscle-invasive Diseasementioning
confidence: 99%